The Dynamics of The Rupiah Exchange Rate in 2017-2020 - Muhammad Arief Aldila Susanto; Rr. Retno Retno Sugiharti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
The exchange rate is one of the most important indicators in the economy. Moreover, with the increasing intensity of trade between countries, commonly referred to as international trade, this economic indicator becomes important for every country, including Indonesia. The change in the Indonesian exchange rate system to a free-floating system has made the exchange rate fluctuations more dynamic. The fluctuations are influenced by various factors, both internal and external. This study aims to determine the effect of the money supply (M2), foreign exchange reserves, SBI interest rates and world crude oil prices on the rupiah/dollar exchange rate in 2017-2020 both in the short run and in the long run. The data used is monthly time series data from 2017-2020. The analytical method used in this study is the Error Correction Model (ECM). The results in this study indicate that in the short run and long run the money supply and foreign exchange reserves variables have a significant effect on the rupiah exchange rate in 2017-2020.